The Functional Crosstalk between HER2 Tyrosine Kinase and TGF-β Signaling in Breast Cancer Malignancy. (24th February 2011) - Wang, Shizhen Emily
Abstract : Accumulating evidence indicates a functional crosstalk between the HER2 (ErbB2) tyrosine kinase and the TGF- β signaling mediated by its serine/threonine kinase receptors. In HER2-overexpressing breast cancer, this crosstalk results in increased cancer cell proliferation, survival and invasion, accelerated cancer progression and metastasis in animal models, and resistance to chemotherapy and HER2-targeted therapy. The transformed cellular context with constitutively active HER2 signaling, as a consequence of HER2 gene amplification or overexpression, converts TGF- β from a tumor suppressor to a malignancy-promoting factor. TGF- β, in turn, potentiates oncogenic HER2 signaling by inducing shedding of the ErbB ligands and clustering of HER2 with integrins. In addition, TGF- β is associated with resistance to trastuzumab, an anti-HER2 therapeutic antibody. Recent mechanistic studies indicate that TGF- β and HER2 cooperate through both Smad-dependent and independent mechanisms. Blockade of HER2:TGF- β crosstalk may significantly enhance the efficiency of conventional therapies in breast cancer patients with HER2 overexpression.